EXAMINING STUDENTS' PERCEPTIONS OF SPEAKING ANXIETY AND ITS INFLUENCE ON ORAL PERFORMANCE IN ENGLISH LANGUAGE LEARNERS - Finza Larasati; Hadiyanto Hadiyanto; Urip Sulistiyo; Eddy Haryanto (University of Kuningan, 2026)
This research aims to explore the perceptions of English Education students at Universitas Muhammadiyah Palembang regarding speaking anxiety in oral communication classes. The anxiety, it appears, stems from challenges such as pronunciation difficulties, vocabulary recall, grammar concerns, and the fear of making mistakes, which could lead to judgment from peers. The study employed a qualitative case study design involving 43 students from the English Education Program at Universitas Muhammadiyah Palembang. Data was collected using a self-developed questionnaire designed to assess the students' perceptions of speaking anxiety and its impact on their performance. The findings reveal that, despite recognizing the importance of English for future career prospects, students' anxiety negatively influences their confidence and effectiveness during speaking activities. The study concludes that speaking anxiety can be mitigated by fostering a supportive and inclusive learning environment. Practical recommendations include integrating both simulated and real-life speaking activities, as well as encouraging students through positive reinforcement to overcome their shyness and actively engage with the language. These approaches can help resolve the issues identified, enabling educators to enhance students' English language skills and better prepare them for the demands of global communication.